2014
DOI: 10.14341/dm2014175-80
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in type 2 diabetes patients treated with insulin: the advantages of continuous glucose monitoring

Abstract: Aims.  To determine the incidence and risk factors for hypoglycemia in elderly insulin-treated type 2 diabetes mellitus (T2DM) patients by means of continuous glucose monitoring (CGM). Materials and Methods.  We observed seventy-six hospitalized patients with T2DM, aged 65 to 79 years. Treatment with basal insulin (n=36), premixed insulin (n=12) or basal-bolus insulin regimen (n=28) was followed by metformin (n=44), glimepiride (n=14) and dipeptidyl peptidase-4 inhibitors (n=14). 2-days CGM with retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
1
0
4
Order By: Relevance
“…Our initial search identified 20 papers, 12,21e39 five studies of which were excludes 21,24,32,38,39 because they compared regimens other than the two specific regimens, two were excluded because they involved Type 1 Diabetes Mellitus patients, 22,34 two were excluded because there was no safety related parameter measured in the study 31,35 and one was excluded due to different injection formulations used for the BB regimen arm. 37 The remaining ten selected studies and their characteristics were analysed as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search identified 20 papers, 12,21e39 five studies of which were excludes 21,24,32,38,39 because they compared regimens other than the two specific regimens, two were excluded because they involved Type 1 Diabetes Mellitus patients, 22,34 two were excluded because there was no safety related parameter measured in the study 31,35 and one was excluded due to different injection formulations used for the BB regimen arm. 37 The remaining ten selected studies and their characteristics were analysed as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…В данном исследовании мы подтвердили данные о достаточно высокой распространенности эпизодов низкого уровня глюкозы, выявляемых с помощью НМГ, у больных СД2, получающих инсулин [21]. Несмотря на сходную суточную дозу инсулина и отсутствие мет-формина, средний уровень глюкозы по данным НМГ у пациенток с СКФ в диапазоне 30-44 мл/мин/1,73 м 2 оказался несколько ниже, чем у больных других групп.…”
Section: Discussionunclassified
“…Большое значение имеют результаты самоконтроля гликемии, занесенные в память глюкометра или в дневник пациента. Для выявления скрытых эпизодов гипогликемии целесообразно провести НМГ [60]. Далее осуществляется индивидуализация целевых значений гликемии (обычно устанавливаются на более высоких цифрах, чем у больных без НРГ).…”
Section: пошаговый подход к ведению больных с нарушением распознаваниunclassified